2020
DOI: 10.1016/j.jhin.2020.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of a Clostridioides difficile ribotype 027 outbreak with a lean intervention bundle

Abstract: Background: In a 2015 point-prevalence study, Clostridioides difficile 027, a hypervirulent ribotype, was absent from healthcare institutions in Switzerland. In late 2016, we detected an outbreak of C. difficile infection (CDI) with ribotype 027 occurring across several hospitals in the same hospital network. Methods: The first cases of CDI due to ribotype 027 triggered an outbreak investigation, including whole genome sequencing (WGS) to identify outbreak strains. Findings: Twenty-eight patients with CDI caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The genomes tend to cluster in ribotype groups. RT027 (n=44) includes isolates from a previously described outbreak ( Kuenzli et al., 2020 ) and shows a maximum diversity between isolates of 12 allelic differences. Within the RT078/126 cluster (n=49), the maximum diversity between two genomes is nine allelic differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genomes tend to cluster in ribotype groups. RT027 (n=44) includes isolates from a previously described outbreak ( Kuenzli et al., 2020 ) and shows a maximum diversity between isolates of 12 allelic differences. Within the RT078/126 cluster (n=49), the maximum diversity between two genomes is nine allelic differences.…”
Section: Resultsmentioning
confidence: 99%
“…An outbreak of RT027 in Switzerland showed that genomes from one center clustered within three allele differences, well within the ≤6 allele cluster limit (Kuenzli et al, 2020). A SNP tree of the outbreak associated isolates showed more than 100 SNP differences between some of the isolates, and in this case the higher resolution was useful in characterizing the outbreak (Kuenzli et al, 2020). In many cases, RT can be predicted from genome assemblies via cgMLST, but sequenced reference genomes are required for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we recommend a threshold of 3 alleles to compensate for any assembly artifacts when less conservative pipelines are used and for outbreaks that last longer than 124 days (36).…”
Section: Discussionmentioning
confidence: 99%